Mapping the IscR regulon sheds light on the regulation of iron homeostasis in Caulobacter - dos Santos, Naara M.; Picinato, Beatriz A.; Santos, Lucas S.; de Araújo, Hugo L.; Balan, Andrea; Koide, Tie; Marques, Marilis V. (Frontiers in Microbiology, 2024)
The role of the iron-sulfur [Fe-S] cluster transcriptional regulator IscR in maintaining [Fe-S] homeostasis in bacteria is still poorly characterized in many groups. Caulobacter crescentus and other Alphaproteobacteria have a single operon encoding [Fe-S] cluster biosynthesis enzymes. We showed that the expression of this operon increases in iron starvation, but not in oxidative stress, and is controlled mainly by IscR. Transcriptome analysis comparing an iscR null mutant strain with the wild-type (wt) strain identified 94 differentially expressed genes (DEGs), with 47 upregulated and 47 downregulated genes in the DiscR mutant. We determined the IscR binding sites in conditions of sufficient or scarce iron by Chromatin Immunoprecipitation followed by DNA sequencing (ChIP-seq), identifying two distinct putative DNA binding motifs. The estimated IscR regulon comprises 302 genes, and direct binding to several regulatory regions was shown by Electrophoresis Mobility Shift Assay (EMSA). The results showed that the IscR and Fur regulons partially overlap and that IscR represses the expression of the respiration regulator FixK, fine-tuning gene regulation in response to iron and redox balance.